Cinematizing the Epic Gaze: Julius Caesar and Pompey in Lucan and in the HBO/BBC Television Series Rome1. (4th January 2021) - Novokhatko, Anna A.
Abstract: In this article I argue that a gaze-oriented analysis of the representations of the protagonists Caesar and Pompey in Lucan's epic The Civil War (written 62–65 ce ) and in the recent television series Rome (broadcast by HBO, BBC Two and Rai 2 between 2005 and 2007) opens new opportunities both for interpreting Lucan's text and for comprehending its reception in the television series. Lucan deliberately employs intensive vocabulary and narrative of vision and visuality when his protagonists appear. In Lucan, Caesar and Pompey are represented, zoomed in upon, and put into action in a cinematic way. The manner in which they see and are seen is crucial for their distinctiveness and determine their function in epic. In the television series, these patterns are taken over and reused within the new technical medium.